Econometric analysis of choice drivers and willingness to pay for certified forest biomasses for energy - Liam Pippinato; Stefano Bruzzese; Raffaele Zanchini; Francesca Poratelli; Simone Blanc; Filippo Brun (Italian Review of Agricultural Economics (REA), 2022)
In the field of fuels generated from renewable resources, woody biomasses have found fertile ground for labelling. Indeed, several certification schemes have been developed, covering not only the sustainability of forest management, but also the chain of custody, allowing the traceability of products at different stages, from production to purchase. This study aims to investigate whether there is a willingness to pay for forest products for energy purposes with sustainability or quality certifications (FSC, PEFC and ENplus certifications) and what determines it, using pellets as reference product for the study. To do so, an exploratory analysis has been conducted, firstly using Principal Component Analysis (PCA) for a dimensional reduction and, subsequently, an ordered logistic regression. The results show that more than 30% of consumers are mainly willing to pay up to 10% more for PEFC and FSC certified pellets than for non-certified products, indicating a strong attention by consumers towards environmental issues, the quality certifications that can be adopted for pellets, and the attitude of consumers towards local and recycled products.
Keywords: M31; 330; pellet; sustainability certification; willingness to pay; quality label